IDENTIFIKASI DAN ANALISIS PERAN STAKEHOLDER PENGELOLAAN SUB DAS NGRANCAH BERKELANJUTAN (STUDI KASUS DI SUB DAS NGRANCAH – KABUPATENKULONPROGO) - Susatyo, Marcus Octavianus; Marsono, Djoko; Kusumandari, Ambar; Supriyanto, Nunuk (Jurnal Wana Tropika, 2015)
Watershed management is part of sustainable national development and its implementation have to synergistically with other development sectors. Coordination among stakeholders is fundamental framework that must be done to achieve the objectives and targets of sustainable watershed management. Ngrancah Sub watershed is the catchment area of Sermo Dam. The area of Ngrancah Sub Watershed is almost 2110 hectares. The existence of vital object, Sermo Dam, signalled the need for Ngrancah Sub Watershed management in a sustainable way. In this regard , need to identification and analysis the role of stakeholders in sustainable Ngrancah Sub Watershed management. The objectives of this research : (1) to identify stakehoders involved in Ngrancah Sub Watershed management; (2) to analyse the role of each stakeholder in Ngrancah Sub Watershed management. Stage analysis : identify all stakeholder involved/interest/influenced in Ngrancah Sub Watershed managament; classify stakeholders based on to their role in operational of Ngrancah Sub Watershed management into 3 categories (Primary, secondary and tertiary); identify each category of stakeholder according to : (1) Characteristic of social and economic status , the structure of the organization , duties and responsibilities;(2) problems : needs, interst, objectives; (3) potency : resources owned, knowledge, experiences; (4) Involvement in the implementation of the program : beneficiary, support, resistence; each stakehoder would be examined, especially for “important” stakeholder in term of influence and the interests of their involvement in Ngrancah Sub Watershd management and its affecting the success of the program.What is meant by interest in here is how problems, needs and interest of stakeholders in line with watershed management. Result of stakehoders identification, there are 23 stakeholders involve in ngrancah sub watershed management which divided into 13 primary stakeholders, 3 secondary stakeholders, and 7 tertiary stakeholders. The success of sustainable management can be done by synergies among stakeholders. Regional Planning Office of Kulon Progo District (BAPPEDA) and Serayu Opak Progo Watershed Management Office become a leading sector in ngrancah sub watershed management. Key Words : Watershed, sustainable watershed management, stakeholder